(untitled) (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Gamlamo Village in West Halmahera Regency holds significant potential for organic waste management, particularly from the Jailolo traditional market. The Bandeng Jaya Fish Farming Group, as the community partner, faces challenges in accessing affordable fish feed and has not yet utilized organic waste effectively. This community service activity aimed to enhance initial knowledge and skills through training in producing fish feed and eco-enzyme liquid fertilizer from organic waste. The implementation included dissemination, technical training, hands-on practice, and evaluation. Statistical analysis using the Wilcoxon matched-pairs signed rank test showed a significant increase in participants’ knowledge scores after training, with p = 0.0001 (p < 0.05). The average pre-test score of 28 rose to 97 in the post-test. The outcomes remain limited to the delivery of materials and training, without full-scale product application. These results indicate that the training was effective in improving participants’ understanding of organic waste processing.